2012
DOI: 10.1007/s00467-012-2211-z
|View full text |Cite
|
Sign up to set email alerts
|

Nortriptyline for treating enuresis in ADHD—a randomized double-blind controlled clinical trial

Abstract: Administration of nortriptyline for treating enuresis in ADHD has not been investigated before. Nortriptyline is statistically superior to placebo. However, enuresis will relapse after stopping nortriptyline in children with ADHD who continue taking methylphenidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In this study, 10 (22.7%) of the test subjects and 17 (39.5%) of the placebo subjects were found to have ADHD [ 31 ]. Ghanizadeh [ 42 ] conducted an RCT with 43 children with comorbid ADHD and nocturnal enuresis, and found that treatment with methylphenidate and nortriptyline was superior to methylphenidate and placebo in reducing nocturnal enuresis events, but there was notable relapse of symptoms once treatment was withdrawn. Increased sphincter tone may have led to the reported urinary retention in one case of an 8-year-old child treated with atomoxetine with ADHD [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 10 (22.7%) of the test subjects and 17 (39.5%) of the placebo subjects were found to have ADHD [ 31 ]. Ghanizadeh [ 42 ] conducted an RCT with 43 children with comorbid ADHD and nocturnal enuresis, and found that treatment with methylphenidate and nortriptyline was superior to methylphenidate and placebo in reducing nocturnal enuresis events, but there was notable relapse of symptoms once treatment was withdrawn. Increased sphincter tone may have led to the reported urinary retention in one case of an 8-year-old child treated with atomoxetine with ADHD [ 43 ].…”
Section: Resultsmentioning
confidence: 99%